2017
DOI: 10.1371/journal.pone.0186078
|View full text |Cite
|
Sign up to set email alerts
|

ERα36, a variant of estrogen receptor α, is predominantly localized in mitochondria of human uterine smooth muscle and leiomyoma cells

Abstract: ERα36 is a naturally occurring, membrane-associated, isoform of estrogen receptor α. The expression of ERα36 is due to alternative splicing and different promoter usage. ERα36 is a dominant-negative effector of ERα66-mediated transactivational activities and has the potential to trigger membrane-initiated mitogenic, nongenomic, estrogen signaling; however, the subcellular localization of ERα36 remains controversial. To determine the cellular localization of ERα36 in estrogen-responsive human uterine smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, the ERα36 mRNA was also found in various healthy estrogen-sensitive tissues such as the mammary gland, the uterus, the bone and cartilage tissues, renal tubules, the stomach, etc. [31][32][33][34][35][36]. This suggested that this variant could participate in mediating the physiological effects of estrogens.…”
Section: Consequences Of Erα36 Expression In Non-cancerous Cellsmentioning
confidence: 96%
“…However, the ERα36 mRNA was also found in various healthy estrogen-sensitive tissues such as the mammary gland, the uterus, the bone and cartilage tissues, renal tubules, the stomach, etc. [31][32][33][34][35][36]. This suggested that this variant could participate in mediating the physiological effects of estrogens.…”
Section: Consequences Of Erα36 Expression In Non-cancerous Cellsmentioning
confidence: 96%
“…Fluorescence images were captured using a confocal laser-scanning microscope (Leica, Solms, Germany). The Image J Just Another Colocalization Plugin (JACoP) was applied for quantitative colocalization analyses [56].…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Estrogen controls various physiological and disease processes, especially reproduction, bone remodeling, and development of gynecologic cancer [2]. This increased occurrence of UEC has been attributed to the most common subtype of UEC, that is, type 1 estrogendependent UEC, which is comprised of grades 1 and 2 endometrioid adenocarcinoma [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This increased occurrence of UEC has been attributed to the most common subtype of UEC, that is, type 1 estrogendependent UEC, which is comprised of grades 1 and 2 endometrioid adenocarcinoma [3,4]. Estrogen receptors (ER) belong to the nuclear receptor superfamily, including estrogen receptor alpha (ERα), estrogen receptor beta (ERβ) and, estrogen-related receptors (ERRα, β, and γ) [2,5,6]. Estrogen triggers the proliferation, invasion and epithelial-mesenchymal transition (EMT) event of uterus endometrial cancer cells (UECC) and contributes to the pathogenesis and progression of UEC [7,8].…”
Section: Introductionmentioning
confidence: 99%